APPLICATION OF NATURAL SOURCES OF NITRITE OF PLANT ORIGIN IN MEAT PROCESSING INDUSTRY - Silovksa NIkolova Aleksandra; Belichovska Daniela (Knowledge International Journal, 2021)
The use of nitrite in meat processing industry is of great technological importance. Nitrites are important as preservatives, due to their inhibitory effect on the growth and development of pathogenic microorganisms, primarily Clostridium botulinum. With their application healthy and safe meat products are placed on the market. On the other hand, they are important for: development and stabilization of the pink - reddish color of processed meat, they act as antioxidants, and through their antioxidant activity, they indirectly affect the improvement of the aroma of the finished product. If nitrites and nitrates are used in excessive amounts, they pose a great risk to human health. However, there is an established legislation on their use, i.e. the maximum allowed concentration is determined, depending on the type of meat product, which eliminates the possibility of their excessive use. The added nitrites react with the meat proteins, thus forming the harmful chemical carcinogens N-nitrosamines. Today, modern consumers are increasingly taking care of their health and starting to change their eating habits. They start looking for meat products with a lower amount of additives. At the same time, consumers begin to prefer the use of natural sources of additives, as opposed to synthetic additives, primarily emphasizing the use of synthetic nitrites used in meat processing. For this purpose, the intake of nitrites in meat products is constantly reduced. Meat processing factories use compounds that inhibit the production of N - nitrosamines and seek natural alternative sources of nitrites. However, it is very difficult to find a suitable substitute. More and more emphasis is put on the use of vegetables that contain large amounts of nitrates, such as carrots, celery, spinach, beets, parsley, chard, etc. Especially the juice and powder of these vegetables contain very high concentrations of nitrites, which can be used in the meat processing industry.
Keywords: nitrites, nitrates, meat products, natural source, vegetable origin